HERMENEUTIKA GADAMER DALAM STUDI TEOLOGI POLITIK - Attamimi, Faisal (Institut Agama Islam Negeri (IAIN) Palu, 2012)
This article discusses Gadamers hermeneutics in the study of political theology. The question of meaning is at the heart of hermeneutic study. The significance or meaning comes from the German word